1990
DOI: 10.1007/bf01907127
|View full text |Cite
|
Sign up to set email alerts
|

Glycolysis in heart failure: a31P-NMR and surface fluorometry study

Abstract: Glycolysis is slow in the heart, especially in the cardiomyopathic heart. Glycolysis is partially rate-limited by phosphofructokinase (PFK), an enzyme which is inhibited by calcium (Ca2+)i and hydrogen ions (H+)i and activated by cAMP. (H+)i and (Ca2+)i are augmented in cardiomyopathy. With glucose as the only substrate (NADH)/(NAD) the phosphorylation potential and developed pressure were significantly lower, and concentrations of phosphomonoester sugars and hydrogen ions (H+)i were significantly higher in is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Diastolic force development, however, is occurring at the same energy expenditure as systolic force generation in human failing myocardium [132]. If indeed, higher energy consumption and, thus, ATP hydrolysis occurs in failing myocardium, but with an insufficient compensatory increase of NADH production by the TCA cycle, this may explain the pronounced oxidation of the NADH-pool in failing hearts [4], which may eventually result in a mismatch between ATP supply and demand. It has been suggested that such a mismatch precedes the reduction in the total cellular levels of PCr in patients with heart failure [11,99,188].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Diastolic force development, however, is occurring at the same energy expenditure as systolic force generation in human failing myocardium [132]. If indeed, higher energy consumption and, thus, ATP hydrolysis occurs in failing myocardium, but with an insufficient compensatory increase of NADH production by the TCA cycle, this may explain the pronounced oxidation of the NADH-pool in failing hearts [4], which may eventually result in a mismatch between ATP supply and demand. It has been suggested that such a mismatch precedes the reduction in the total cellular levels of PCr in patients with heart failure [11,99,188].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, both the reduced amplitude of cytosolic Ca 2+ transients [59] and elevated [Na + ] i [117] may hamper Ca 2+ -activation of TCA cycle enzymes in heart failure. Furthermore, glycolysis and, thus, the availability of pyruvate as a substrate for the TCA cycle was reduced in myopathic compared to control hamsters, resulting in more oxidized NADH and decreased phosphorylation potential and developed LV pressure [4]. Application of pyruvate in this model improved both energetic and hemodynamic parameters [4].…”
Section: Pathophysiological Aspects Defects In Ec Coupling In Chronicmentioning
confidence: 93%
See 2 more Smart Citations
“…In fact, the availability of different substrates has a profound influence on the function of the diseased myocardium [13]. Supplying energy substrates, such as pyruvate, to the failing myocardium markedly improves contractile performance [24]. Also, enhanced glycolysis within cardiomyocytes increases the supply of substrates to mitochondria and promotes ATP production [25].…”
Section: Oxygen and Substrate Supplymentioning
confidence: 99%